FACTORS OF COMPETITIVENESS OF UNIVERSITIES UNDER GLOBALIZATION OF EDUCATIONAL MARKETS - Zoya HALUSHKA; Valeriy SOBOLEV (USV Annals of Economics and Public Administration, 2016)
We define modern requirements for university education, factors affecting the competitiveness of universities under globalization. The role of Ukrainian universities in ensuring of the competitiveness of the national economy is characterized. We propose to take into account the national peculiarities of social development in developing competitive strategies of universities.